Flood inundation modeling and hazard mapping under uncertainty in the Sungai Johor Basin, Malaysia - Ali, Anuar Bin Md. (Boca Raton, FL : CRC Press, 2018)
"Flooding can have devastating impacts on peoples livelihood, economy and the environment. One way to minimize flood losses is using floodplain maps, which assist land planners and local authorities in identifying flood-prone areas, and provide useful information for rescue and relief agencies for their operations. Developing floodplain maps often involves flood inundation modeling. This typically requires precipitation and stream flow data, topographic information, the selection of a hydraulic model and the calibration of its parameters. A common representation of floodplain map is based on a single outcome without an explicit consideration of all the sources of uncertainty in the modeling process. The research presented in this thesis addresses the uncertainty in the flood inundation modeling, which may arise from input data and hydraulic modeling approach. The study area is the Sungai Johor basin in Johor, Malaysia, which is an agricultural dominated area.By using a set of sample data for Sungai Johor Basin, the case study show the uncertainties arising from an estimation of design flow, terrain data sets, geometric description in hydraulic models and different modeling approaches.The intent of the research in flood inundation maps is to emphasize the impact of uncertainties in flood inundation maps that not only provide useful results but also suggested further research and improvement of flood inundation mapping practices."--Provided by publisher.
chapter 1 Introduction -- chapter 2 Literature review -- chapter 3 Study area and data availability -- chapter 41 D hydraulic modelling: the role of cross-sections spacing -- chapter 52 D hydraulic modelling: the role of digital elevation models -- chapter 61 D hydraulic modelling: the role of digital elevation models -- chapter 7 Uncertainty in simulating design flood profiles and inundation maps on the Johor River, Malaysia -- chapter 8 Conclusions and recommendations.
Keywords: Flood forecasting -- Malaysia; Floods -- Malaysia